2002
DOI: 10.1038/sj.sc.3101236
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of painful spasticity after spinal cord injury

Abstract: Study design: There are several conservative methods of painful spasticity treatment. However, conservative methods do not always provide long-term and complete antispastic e ects in cases of spinal cord injury with severe painful spasticity. Objectives: The aim of the present study was to analyse and compare the e ectiveness of myelotomy by Bischof II and Pourpre in patients with paraplegia and severe painful spasticity in the late period after spinal cord trauma. Setting: Spinal Care Unit, Meir General Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Unfortunately, the costs from the PROCESS trial 115 neurologist, orthopaedic surgeon and followup during trial (nurse) costs. The investigation cost consists of computed tomography, magnetic resonance imaging, radiography and myelography.…”
Section: Scs Costsmentioning
confidence: 99%
“…Unfortunately, the costs from the PROCESS trial 115 neurologist, orthopaedic surgeon and followup during trial (nurse) costs. The investigation cost consists of computed tomography, magnetic resonance imaging, radiography and myelography.…”
Section: Scs Costsmentioning
confidence: 99%
“…16 Contusion was induced on laminectomized animals and muscle spasticity was determined by evaluating muscle tone and muscle spasm according to the Ashworth and spasm–frequency scales. 25 Post-operative care was performed including manually assisted extrusion and analgesia. BoT-A Botox was diluted with 2 mL of saline and a solution was prepared with 6 U of toxin per 0.1 mL.…”
Section: Methodsmentioning
confidence: 99%
“…Livshits et al 72 report in a case-control study comparing the Pourpre versus Bischof II approaches and assesses the effectiveness of reducing pain and refractory spasticity in patients with SCI (N = 40), the follow-up at 6 months, 5 and 10 years using the McGill Pain Questionnaire, the current intensity scale of the pain and the visual analogue scale (VAS) to assess control and improvement of pain, found that both techniques are effective for this purpose, however, with more significant results with the Pourpre technique. 72 There is level 3 evidence from a case-control study to support the use of longitudinal myelotomy to decrease spasticity with pain in patients with SCI. 72,73 The main indications for myelotomy are in patients with abdominal or pelvic visceral pain secondary to cancer.…”
Section: ) Dorsal Longitudinal T-myelotomy For Pain Management Aftermentioning
confidence: 99%
“…72 There is level 3 evidence from a case-control study to support the use of longitudinal myelotomy to decrease spasticity with pain in patients with SCI. 72,73 The main indications for myelotomy are in patients with abdominal or pelvic visceral pain secondary to cancer.…”
Section: ) Dorsal Longitudinal T-myelotomy For Pain Management Aftermentioning
confidence: 99%